Dengue outbreak in 1998 - Terengganu experience - ﻿Nor Azimi, Y., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
The aim of this study was to describe a dengue outbreak in 1998, the worst ever reported in Terengganu. All cases notified to the Vector Borne Diseases Control Unit, Terengganu State Health Department was included in this study and information provided in the notification forms were analysed. A total of 2060 dengue cases with 4 deaths were reported in that year, with an increase of 267.9%. Out of the 2060 reported cases, 1907 (92.6%) were dengue fever with the remaining 153 (7.4%) being dengue haemorrhagic fever. The outbreak peaked in the second half of the year between August and October and subsequently declined until the 10th week of 1999. A total of 1216 (59.0%) of the reported cases had IGM to dengue demonstrated in at least one serum sample. 652 (53.6%) of these cases were confined to urban areas while 564 (46.4%) were from rural areas. 611 (50.2%) were females and the majority of the patients were Malays. The average days taken for a patient to be admitted to a hospital from the date of onset was about 4.24 days and the average days taken for the blood specimen for dengue IGM to be taken from the date of onset was 5.05 days. A total of 193281 premises were inspected for Aedes larvae, of which 1347 were positive. A total of 1155 fines were issued amounting of RM 35,455 and 1705 notices were issued in that year. The factors relating to statistically significant Dengue IGM were gender, day after onset when the blood specimen was taken, the platelet counts and packed cell volume (PCV) as well as type of Dengue Fever. (P<0.05). Blood specimens for dengue IGM should be taken at the appropriate time, as this will determine the outcome of the result, which subsequently affects management decisions.